Short message service cancellation intervention to reduce integrated sexual health and HIV 'did not attend' appointment rates. (February 2019) - Tomkins, Andrew; Naylor, Sam; Morgan, Emile
Did not attend (DNA) appointments create a significant impact upon resource and finance efficiency in the NHS. Despite introduction of short-message service (SMS) reminders to our patients, DNA rates remained persistently high. An option to send an SMS to cancel a booked appointment was piloted from 15 January to 16 April 2018 for integrated sexual health and human immunodeficiency virus (HIV) appointments. Absolute monthly mean DNA rates as a proportion of total bookable appointments fell by 2.24% (14.42% pre-intervention [95% CI: 13.15–15.79%] to 12.18% post-intervention [95% CI: 10.98–13.50%]). Cancellation rates increased proportionally by 14.28% from 24.4% to 38.68% (786/3224 pre-intervention [95% CI: 22.70%–26.15%] to 1184/3061 post-intervention [95% CI: 36.52–40.93%]). Findings suggest that SMS cancellations are a viable solution to reduce DNA rates in this setting.